Black rodeo : a history of the African American western - Mask, Mia, 1969- (University of Illinois Press, 2023)
"African American westerns have a rich cinematic history and visual culture. Mia Mask examines the African American western hero within the larger context of film history by considering how Black westerns evolved and approached wide-ranging goals. Woody Strode's 1950s transformation from football star to actor was the harbinger of hard-edged western heroes later played by Jim Brown and Fred Williamson. Sidney Poitier's Buck and the Preacher provided a narrative helmed by a groundbreaking African American director and offered unconventionally rich roles for women. Mask moves from these discussions to consider blaxploitation westerns and an analysis of Jeff Kanew's hard-to-find 1972 documentary about an all-Black rodeo. The book addresses how these movies set the stage for modern-day westploitation films like Django Unchained. A first-of-its kind survey, Black Rodeo illuminates the figure of the Black cowboy while examining the intersection of African American film history and the western"--